What are the effects of AEBS on collision avoidance? - Rost, Louise; Sällberg, Joakim (My University, 2019)
Advanced Emergency Braking System (AEBS) is an active safety system for Heavy Goods Vehicles (HGVs) which aims to prevent rear-end collisions, i.e. when a vehicle drives into the rear of the vehicle in front. This report investigates the performance of AEBS in Volvo HGVs, and describes under what circumstances the system intervenes correctly and incorrectly respectively. Data from AEBS interventions by Volvo HGVs was analysed, and patterns of the incorrect interventions were identified. These patterns were translated into code, resulting in a program that automatically classifies the logged interventions as correct or incorrect. Different variables were investigated for the correct and incorrect interventions separately, for the purpose of finding factors that affect the performance of AEBS, i.e. under which circumstances the correct and the incorrect interventions occur. The majority of the incorrect interventions were found to be due to stationary targets, and only resulted in a short intervention with minor speed reduction. Therefore, it seems very unlikely that the incorrect interventions would cause collisions. The majority of the interventions were found to be true, and many of these interventions yielded a large speed reduction. Thus, AEBS interventions prevents many collisions.
Keywords: Transport; Hållbar utveckling; Databaser; Databehandling; Signalbehandling; Farkostteknik; Transport; Sustainable Development; Databases; Data processing; Signal Processing; Vehicle Engineering